#### Answer

$y' = -\frac{3}{5}x^{-\frac{8}{5}}$

#### Work Step by Step

$y = x^{-\frac{3}{5}} + \pi^{\frac{3}{2}}$
$y' = -\frac{3}{5}x^{-\frac{8}{5}} + 0 $
$y' = -\frac{3}{5}x^{-\frac{8}{5}}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = -\frac{3}{5}x^{-\frac{8}{5}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.